Outcome in dedifferentiated chondrosarcoma for patients treated with multimodal therapy: Results from the EUROpean Bone Over 40 Sarcoma Study. (July 2021) - Hompland, Ivar; Ferrari, Stefano; Bielack, Stefan; Palmerini, Emanuela; Hall, Kirsten S.; Picci, Pierro; Hecker-Nolting, Stefanie; Donati, Davide M.; Blattmann, Claudia; Bjerkehagen, Bodil; Staals, Eric; Kager, Leo; et al.
Abstract: Introduction: The role of chemotherapy for patients with dedifferentiated chondrosarcoma (DDCS) is still under discussion. Here, we present the outcome in patients with DDCS treated with intensive chemotherapy from the EUROpean Bone Over 40 Sarcoma Study. Materials and methods: The chemotherapy regimen included doxorubicin, ifosfamide and cisplatin. Postoperative methotrexate was added in case of poor histological response. Toxicity was graded based on the National Cancer Institute expanded common toxicity criteria, version 2.0, and survival was analysed using Kaplan-Meier curves, log-rank tests and univariate Cox regression models. Results: Fifty-seven patients with DDCS (localised, 34 [60%]; metastatic, 23 [40%]) aged 42–65 years were included. Surgical complete remission (SCR) was achieved in 36 (63%) patients. The median overall survival (OS) was 24 months (95% confidence interval, 22–25), and the 5-year OS was 39%. Patients with extremity localisation had a 5-year OS of 49% compared with 29% in patients with a central tumour ( P  = 0.08). Patients with localised disease had a 5-year OS of 46%, whereas patients with metastatic disease had a 5-year OS of 29% ( P  = 0.12). Patients in SCR had a 5-year OS of 49%, whereas patients not in SCR had a 5-year OS of 23% ( P  = 0.004). Chemotherapy toxicity was considerable but manageable. There was no treatment-related death, and 39 (70%) patients received ≥6 cycles of the planned nine chemotherapy cycles. Conclusions: Adding intensive chemotherapy to surgery for treatment of DDCS is feasible and shows favourable survival data compared with previous reports. With the limitations of data from a non-controlled trial, we conclude that chemotherapy could be considered in the management of patients aged >40 years. Highlights: This is the first prospective study conducted on patients with dedifferentiated chondrosarcoma. Addition of chemotherapy to surgery was feasible. Chemotherapy gave favourable survival compared with previous retrospective studies. Almost half of the patients in complete surgical remission were alive.